1988
DOI: 10.1017/s0031182000058388
|View full text |Cite
|
Sign up to set email alerts
|

Integrated control of ticks and tick-borne diseases of cattle in Africa

Abstract: The problems caused by tick and tick-borne diseases for livestock particularly cattle on the African continent are described and discussed. The control of ticks and tick-borne diseases must receive high priority in Africa with regard to both research and control application because of their widespread distribution in areas of high livestock potential and productivity. The conventional methods of tick and tick-borne disease control are discussed and are found to be inadequate in the conditions prevailing in Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 122 publications
(134 reference statements)
0
66
0
Order By: Relevance
“…The types of chemicals used for tick vector control are summarized in Table X. Vector control is associated with the following problems: the high cost of acaricides; vulnerability of tick control programs to political and economic instability [11, 52-54, 78, 83]; acquired resistance to acaricides in Zambia and many other countries [4, 5, 27, 40-42, 92, 94, 95, 102, 108, 109]; destabilization of the endemic stability; environmental pollution and residues in animal products [35,[110][111][112]. More studies to better understand the resistance mechanisms in ticks and their diagnosis need to be carried out.…”
Section: Vector Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The types of chemicals used for tick vector control are summarized in Table X. Vector control is associated with the following problems: the high cost of acaricides; vulnerability of tick control programs to political and economic instability [11, 52-54, 78, 83]; acquired resistance to acaricides in Zambia and many other countries [4, 5, 27, 40-42, 92, 94, 95, 102, 108, 109]; destabilization of the endemic stability; environmental pollution and residues in animal products [35,[110][111][112]. More studies to better understand the resistance mechanisms in ticks and their diagnosis need to be carried out.…”
Section: Vector Controlmentioning
confidence: 99%
“…Studies have shown that immunized cattle are protected against challenge provided the appropriate parasite stocks are used [91,112]. It is also known that immunized cattle as well as those that recover naturally from ECF/ CD are carriers of the infection and therefore, can serve as a source of infection for others [22,23,39,45,112]. These vaccines are poorly adopted in the region, mainly because of problems associated with the use of live parasites.…”
Section: Theileriosismentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated annual global costs associated with ticks and tick-transmitted pathogens in cattle amounted to between US$ 13.9 billion and US$ 18.7 billion [1]. In Africa, tick-borne diseases are considered the most important animal disease problem [2]. In Australia, it has been estimated that the losses due to cattle ticks, except for the wounding and rendering of animals susceptible to myiasis, are 65% related to anorexia and 35% related to blood loss [3].…”
Section: Introductionmentioning
confidence: 99%
“…Beside the transmission of Theileria parva, this tick causes impor tant economic losses by its massive infestation (Young et al, 1988). To control tick populations, the use of acaricides is still the only efficient way, but the appearance of resis tant strains to most acaricides available limits the use of this approach to tick control (Nolan, 1985;Riddles and Nolan, 1987).…”
Section: Introductionmentioning
confidence: 99%